2023
DOI: 10.3390/toxics11060533
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Influence of Sublethal Exposure to Sulfoxaflor on the Aphidophagous Predator Hippodamia variegata (Coleoptera: Coccinellidae)

Abstract: Hippodamia variegata (Goeze), the variegated ladybug, is a predator of many insect pests, especially aphids. Sulfoxaflor is a chemical insecticide that can be used to control many sap-feeding insect pests, for instance, plant bugs and aphids, as an alternative to neonicotinoids in different crops. To improve the combination of the H. variegata and sulfoxaflor in an IPM (integrated pest management) program, we studied the ecological toxicity of the insecticide to the coccinellid predator at sublethal and lethal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…septempunctata and Hippodamia variegate (Coleoptera: Coccinellidae) (Skouras et al, 2023a;Wang et al, 2023). This phenomenon was not observed in the present study, probably due to the different test methods.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…septempunctata and Hippodamia variegate (Coleoptera: Coccinellidae) (Skouras et al, 2023a;Wang et al, 2023). This phenomenon was not observed in the present study, probably due to the different test methods.…”
Section: Discussioncontrasting
confidence: 74%
“…Similarly, the sublethal dose of imidacloprid treatment had no adverse effect on preadult survival rate, GRR , r , R 0 , λ , and only prolonged T of C. pallens (Su et al, 2023). In addition, it was found that sublethal doses of sulfoxaflor significantly reduced the population parameters of C. septempunctata and Hippodamia variegate (Coleoptera: Coccinellidae) (Skouras et al, 2023a; Wang et al, 2023). This phenomenon was not observed in the present study, probably due to the different test methods.…”
Section: Discussionmentioning
confidence: 99%